Unsur polisemi Bahasa Melayu dalam perbualan generasi muda - Yop Othman, Zul Hanis; Husain, Salina; Bolhassan, Nabillah (University of Melaka, 2022)
This study focuses on the word polysemy in the conversation of the young generation. The objective of the study is to identify and analyze the elements of polysemy in the conversation of the young generation by applying the theory of Meaning Component Analysis by Nida (1975). Previous polysemy studies have not emphasized the study of polysemy in community conversation. Data were analyzed qualitatively through spontaneous and random conversation recordings using the young generation respondents aged 28 to 34 years in a restaurant. The results of the study found that the word polysemy can be explained meaning by using the meaning component of the feature / + / has meaning and / - / has no meaning for the word. Therefore, this study can explain the meaning of the word polysemy according to the context of the background in the conversation.